Foundations and best practices in early childhood education : history, theories, and approaches to learning - Follari, Lissanna M. (Boston : Pearson, 2011)
"A broad exploration of the roles and practices of working with, and for, children and families Foundations and Best Practices in Early Childhood Education helps teachers connect early childhood education beliefs and philosophies to professional practice. It provides insights into common program models or approaches, including Reggio Emilia, Montessori, High/Scope, Head Start, Waldorf, and The Project Approach. Real classroom stories illustrate how teachers and programs integrate child-centered approaches into actual practice. Running themes emphasize teachers$1 (Broles, views of children, inclusion, and diversity. New and experienced teachers alike will learn to define, shape, and reshape their own practices to advocate on behalf of children and families." -- Provided by publisher. s
Includes bibliographical references and index.
Keywords: Early childhood education